A green approach to the analysis of co-administered ampicillin/sulbactam and paracetamol in human urine - SELIM BASMA M.; ABDELSALAM RANDA A.; EL-GINDY ALAA; EID BASMA G.; NEAMATALLAH THIKRYAT; KHAYYAT AHDAB N.; HADAD GHADA M.; ELKHOUDARY MAHMOUD M. (Acta Pharmaceutica)
The novelty of this work is the simultaneous analysis of sulbactam (SUL), ampicillin (AMP), and paracetamol (PARA) in human urine samples, using the environmentally benign RP-HPLC method. A C18 column was used in chromatographic separation using potassium dihydrogen phosphate (10 mmol L–1, pH 5)/ethanol (90 %, V/V) as the mobile phase; flow rate was 1.00 mL min–1. UV detection at 220 nm was used for quantification. The proposed method showed good linearity in the concentration ranges of 2.20–250.00 μg mL–1 for SUL, 2.50–250.00 μg mL–1 for PARA, and 14.50–250.00 μg mL–1 for AMP. Direct injection of urine samples with no prior extraction was performed. This method was found successful in moving towards greener studies of drugs’ urinary excretion, by decreasing hazardous solvent consumption and waste. Moreover, the method was applied to investigate the urinary excretion of the drugs and possible interaction between ampicillin and paracetamol.